(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In building, high-strength concrete (HSC) is frequently utilized. Although high-strength concrete has a high compressive strength, it has issues with flexural strength and cracking. Fire affects reinforced concrete (RC) members because it increases the bulk temperature of the concrete. This rise in temperature significantly reduces the mechanical qualities of concrete and steel. Transient creep, thermal creep, and other strains are also brought on by fire temperatures. Reviewing previous research on the impact of high temperatures on the flexural strength and durability of high-strength concrete beams is one of the study’s goals. According to study findings, concrete spalling, mass reduction, and durability are critical markers for assessing HPC’s mechanical performance at high temperatures. HPC’s mechanical performance declined as the exposure temperature rose. Furthermore, weight loss rose nonlinearly with the maximum temperature, and concrete’s strength decreased with abrupt cooling.